PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, KOMPENSASI, DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA LPD KEROBOKAN - Daniati, Ni Luh Helga; Mujiati, Ni Wayan (E-Jurnal Manajemen; Vol 7 No 7 (2018), 2018)
Job satisfaction is a criterion to determine the success of the company to meet the needs of its employees. This study was conducted to determine the effect of Transformational Leadership Style, Compensation, and Work Environment on Employee Job Satisfaction. This research was conducted at Kerobokan Traditional Rural Credit Institution by taking samples of 56 people. Data collection was done in two ways, namely interview and questionnaire distribution. Data analysis technique used is multiple linear regression and t test. The results of this study indicate that the style of transformational leadership, compensation, and work environment positively affect employee job satisfaction. Suggestion from this research that a leader must apply transformational leadership style in order to be able to improve employee work satisfaction, compensation must be given in accordance with work load and achievement of employees, and work environment must be kept comfort and kekondusifannya.